Overweight and associated factors in young adult student girls - Raquel Rodrigues da Costa; Thereza Maria Magalhães Moreira; Raquel Sampaio Florêncio; Vera Lúcia Mendes de Paula Pessoa; Virna Ribeiro Feitosa Cestari; Francisca Gomes Montesuma
ABSTRACT Objective: To analyze overweight and associated factors in young adult student girls children in a capital city of Northeast Brazil. Method: An analytical, quantitative study was conducted with 546 young adults from 26 schools in a capital city of the Brazilian Northeast. After obtaining the data by the application of a specific questionnaire, the hierarchical logistic regression was used to identify the confounding variables and predictors of overweight. Results: The frequency of cases of overweight in this group was 36.6%. In the bivariate analysis, Overweight presented a statistically significant association with ethnicity, marital status, weight in childhood and overweight in adolescence, overweight in the family and exposure to alcohol, number of children, and age of menarche. In the final regression model, overweight remained associated with weight in childhood and age of menarche. Conclusion: Characteristics related to nutritional status in earlier life stages and gynecological issues were associated with Overweight during the young adult stage of the woman.